(NdITQ^A PSIHOLOG)QÆQ (B:s)E (NNAW^ALXNIJ POS)QÆBNIK (B/s)E - (NpAWELK)QÆW(B, (NrOMAN wOLODIMIROWI^(B,s)E; (NcIGIPALO(B, (No(B. (Np(B.s ((NkI)QÇW (B:s)E (NaKADEMWIDAW(B,s, 2010)
(NsUTN)QÆSTX(B, (NOSNOWNÆ ZASADI(B, (NMETODI DITQ^OÇ PSIHOLOGÆÇ TA ÇÇ ZNA^ENNQ W DÆQLXNOSTÆ WIHOWATELQ DO[KÆLXNOGO NAW^ALXNOGO ZAKLADU(B.s)E
(NtERM)QÆNOL(B. (NSLOW(B.: (NS(B. 423-428. - (Nl(B-(NRA(B: (NS(B. 429-431s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NpSIHOLOG)QÆQ(B, (NDITQ^As)E; (NPSIH)QÆ^NIJ ROZWITOK DITINIs)E; (NMETODI DITQ^O)QÇ PSIHOLOGÆÇs)E; (NKOGN)QÆTIWNIJ ROZWITOK DITINIs)E; (NPREDMETNA D)QÆQLXNÆSTXs)E; (NSP)QÆLKUWANNQ DITINIs)E; (NOB]ENIE REBENKAs; (NMOWLENN)QÃWIJ ROZWITOK NEMOWLQTIs)E; (NFORMUWANNQ OSOBISTOST)QÆs)E; )QÆ(NGROWA DÆQLXNÆSTX DO[KÆLXNIKAs)E; (NZOBRAVUWALXNA D)QÆQLXNÆSTX DO[KÆLXNIKAs)E; (NTRUDOWA D)QÆQLXNÆSTX DO[KÆLXNIKAs)E; (NNAW^ALXNA D)QÆQLXNÆSTX DO[KÆLXNIKAs)E; (NDITQ^)QÆ KONFLÆKTIs)E; (NUWAGA DO[K)QÆLXNIKÆWs)E; (NMISLENNQ DO[K)QÆLXNIKÆWs)E; (NPAM(B'(NQTX DO[K)QÆLXNIKÆWs)E; (NUQWA DO[K)QÆLXNIKÆWs)E; (NROZWITOK OSOBISTOST)QÆ DO[KÆLXNIKÆWs)E; (NMORALXNIJ ROZWITOK DITINIs; (NTEMPERAMENT DO[K)QÆLXNIKÆWs)E; (NHARAKTER DO[K)QÆLXNIKÆWs)E; (NZD)QÆBNOSTÆ DO[KÆLXNIKÆWs)E; (NGOTOWN)QÆSTX DO [KOLIs)E; (NMOWLENNQ DO[K)QÆLXNIKÆWs)E; (NRE^X DO[KOLXNIKOWs; (NSENSORNIJ ROZWITOK DO[K)QÆLXNIKÆWs)E; (NPO^UTTQ DO[K)QÆLXNIKÆWs)E; (NEMOC)QÆÇ DO[KÆLXNIKÆWs)E; (NMOTIWAC)QÆJNA SFERA DO[KÆLXNIKÆWs)E